2011
DOI: 10.1016/j.jtcvs.2010.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Cold blood spinoplegia under motor-evoked potential monitoring during thoracic aortic surgery

Abstract: Cold blood infusion accelerates motor-evoked potential changes and might enable decision making regarding the need for reconstruction of multidetector computed tomography-defined Adamkiewicz arteries. Cold blood-loaded motor-evoked potential is beneficial to minimize Adamkiewicz artery reconstruction time and limit spinal cord ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…[86][87][88][89][90][91][92][93][94][95][96][97] Preoperative identification of the artery of Adamkiewicz by magnetic resonance angiography or computed tomography-angiography further helps to prevent SCI. 29,[98][99][100][101] TEVAR has recently been increasingly utilized in the management of thoracic aortic aneurysms. Because SCI is also associated with TEVAR, we included TEVAR along with open repairs during our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[86][87][88][89][90][91][92][93][94][95][96][97] Preoperative identification of the artery of Adamkiewicz by magnetic resonance angiography or computed tomography-angiography further helps to prevent SCI. 29,[98][99][100][101] TEVAR has recently been increasingly utilized in the management of thoracic aortic aneurysms. Because SCI is also associated with TEVAR, we included TEVAR along with open repairs during our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, most previous studies related to MEP monitoring during thoracic and thoracoabdominal aortic repair concerned decreased MEP. Significant MEP decrease was defined as an MEP amplitude to less than 50% or 25% of the baseline, and MEP increase was defined as a restoration of MEP followed by aortic intervention and an MEP decrease [3]. In this situation, what does MEP increase imply?…”
Section: Invited Commentarymentioning
confidence: 99%
“…Takahashi et al showed that segmental cold blood infusion, which accelerates a decline in MEPs, is useful for determining when specific arteries need to be reconstructed (e.g., artery of Adamkiewicz). This technique was found to minimize reconstruction time and limit spinal cord damage (Takahashi et al, 2011).…”
Section: )mentioning
confidence: 99%